The Use of Importance Performance Analysis (IPA) of Dental Health Services: A Systematic Review for Health Promotion Strategies - A Agum Aripratama Arsunan; Fuad Husain Akbar; Acing Habibie Mude; Edy Machmud; Eddy Heriyanto Habar; Muhammad Ikbal; A Arsunan Arsin; Aisyah Aisyah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Dental and oral health services are essential for promoting not only physical health but also psychological well-being and patient confidence. Patient satisfaction is a crucial metric of healthcare quality, and the SERVQUAL dimensions—Tangibles, Reliability, Responsiveness, Assurance, and Empathy—serve as a foundation for service evaluation. Importance Performance Analysis (IPA) is an effective method for identifying gaps between patients' expectations and the actual performance of dental services, offering a strategic basis for service improvement. Methods: This systematic review followed the PRISMA 2020 guidelines. Literature was identified through searches in PubMed, Scopus, and Google Scholar using relevant Boolean keywords. A total of 150 articles were initially retrieved. After applying inclusion and exclusion criteria, 10 eligible studies were analyzed. Data were synthesized based on study focus, key findings, moderating factors, and geographic context. Results: The review revealed significant performance gaps in the dimensions of Responsiveness and Empathy, especially in developing countries such as Indonesia, Iran, and Iraq. Contributing factors included limited resources, cultural communication barriers, and disparities in healthcare access. Tangibles such as facility cleanliness and design were also influential in patient satisfaction. Reliability and Assurance contributed to trust-building, though they showed relatively smaller gaps. Studies from high-resource settings demonstrated better overall balance across SERVQUAL dimensions, highlighting the role of institutional support and training. Conclusion: IPA serves as a powerful diagnostic and strategic tool for evaluating and enhancing the quality of dental and oral health services. By highlighting critical performance gaps—particularly in interpersonal and environmental aspects—IPA supports targeted interventions. The integration of patient-centered care principles with IPA findings can guide resource allocation, improve patient satisfaction, and address systemic inequalities in dental healthcare delivery. This review underscores the need for contextualized quality improvement strategies, especially in low-resource environments.